Implementasi Integrasi Islam dan Kedokteran Dalam Tugas Akhir Mahasiswa (Skripsi) Pada Fakultas Kedokteran dan Ilmu Kesehatan UIN Maulana Malik Ibrahim Malang - Nashichuddin, Ach.; Ningsih, Anita Andriya; Toifah, Nur (Journal of Islamic Medicine, 2022)
Background: The integration of Islam and science is the process of unification of various branches of science that exist with an assumption that all components of science come from God, which can be implemented in the learning curriculum in all faculties, including the faculty of medicine and health Sciences in the doctor's education study program. To achieve the vision of realising an integrative doctorate education study program in combining science and Islam of international repute, the integration is implemented in several fields of Education and teaching, including writing the final student project (thesis). Objective : to know the concept of integration of Islam and medicine and its implementation in writing student thesis at the faculty of medicine in ptkin environment. Method: This study uses a qualitative descriptive model to describe the concept of Islamic integration and prayer and its implementation in student thesis in the Medical Education Study Program of the Faculty of Medicine and Health Sciences by sampling ten student thesis in 2020. The results of the study are: 1) The concept used in the integration of Islam and medicine in the final project of students is a model of integration of Islamic Science, which makes the Qur'an and Hadith the foundation of the development of medical science. 2) The concept of integration of Islam and Medicine set out in the thesis writing manual has not been implemented optimally because there are differences in the writing of integration concepts in their final project. Conclusion: The implementation of Islamic Integration and Medicine has not been conceptualized optimally in preparing the final student project (thesis) at the Faculty of Medicine and Health Sciences UIN Maulana Malik Ibrahim Malang. Keywords: Medicine, Integration, Islam